KARAKTER ELEMEN PEMBENTUK BANGUNAN DALAM KARYA ARSITEK SANTIAGO CALATRAVA - , ASPIN, S.PdT ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In a century was dominated by the skill with specialization and the fragmentation, Santiago Calatrava is one of a few designers that is different from general. A number of building design, project engineering, sculpture, and furniture is consistently created the poetry that combines the morphology of structures and movements. Santiago Calatrava backgrounds with a variety of scientific disciplines had: a sculptor, painters, architecture and civil engineering provides combination which is very meaningful to realize a form of its architecture design. Research on character-forming elements of a building in the work of architect Santiago Calatrava aims to determine the character of Santiago Calatrava building elements forming the terms of five aspects of the parameters, namely: (1) technical aspects, (2) aspects of the form, (3) aspects of space, (4) aspects of function, and (5) aspects of the context. In addition this study also aimed to determine factors that influence the character of the building forming element in the architecture of Santiago Calatrava. Studies review in this research conducted by rationalistic approach and method of content analysis. This method contains the cases raised by the data in the form of textual discourses and images that represent the formulation in assessing the character of the building forming elements and factors that influence the character-forming elements of the building. The results based on the parameters character-forming elements of buildings on five cases the object of research, namely-Satolas Lyon TGV Station, Valencia City of Arts and Sciences, Tenerife Concert Hall, Milwaukee Art Museum, and the Turning Torso showed that some of the character of the building forming element in the work of Santiago Calatrava , namely: (1) The structure used to generate architectural form and function as an architectural structure, is used to describe the relationship between structure and architecture in which the structural requirements are allowed to influence the shape of the building is very strong even though the structure is exposed, (2) the dominance of material concrete, steel and glass, which is processed by Calatrava is not common to produce a form corresponding with the analogy of form, (3) analogy as a thematic design, where form is present always monumental and iconic, (4) line element as an element and the shape of the building facade. Neutral colored was dominated of white, (5) the flexibility of space and function to shape and the structure of system, (6) the orientation of context, climate and area landmarks. Calatrava ideas about the movement is a factor that affects the character of the buildings forming element, namely Calatrava like a human form, he explained that the first thing that comes in his mind when he saw human is a movement. Although the buildings he works there are certain parts of buildings are made to move but the movement in question is more to the impression of movement in the building.